PERFORMANCE MEASUREMENT SYSTEMS IN ENGINEERING ORGANISATIONS - Swart, Caitlin; Zincume, Philani (The South African Journal of Industrial Engineering, 2024)
Performance measurement systems (PMSs) are vital for quantifying organisational efficiency and effectiveness, empowering decision-makers to manage processes for operational, and strategic realisation. Despite extensive research, difficulties with implementation persist, impeding institutionalisation. While the factors influencing PMS implementation have been studied, research specific to engineering organisations is limited. This paper employs a bibliometric analysis to confirm PMSs’ relevance in modern organisational contexts and explores a metric, a quantitative tool, for equipment performance evaluation. Twenty-one prevalent implementation factors, categorised under the ‘6Ms’ of production, are identified from the literature. These factors are substantiated for the modern engineering domain using detrimental implementation factors unearthed in Company X, a South African dairy product producer. The resolution of these factors, particularly related to data in Company X, is proposed through a Microsoft Excel workbook facilitating overall equipment effectiveness (OEE) calculations. This validated and refined solution enhances PMS effectiveness, converting data into actionable information for management benefits.